Implementation of the Internet of Things in Energy Budget Efficiency in the OPD of Semarang City - Wardhana, Chrisna Satya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research reviews the potential and strategies for implementing the Internet of Things (IoT) in increasing the efficiency of energy use and reducing the energy budget in Semarang City Regional Apparatus Organizations (OPD). The research method used is qualitative with data collection techniques through interviews, observation, and documentation. The research results show that IoT has great potential to increase energy efficiency in the Semarang City OPD. This potential can be optimized through several strategies, such as building integrated IoT infrastructure, implementing energy monitoring and control systems, using energy-saving devices, and increasing awareness and education of energy users.